Magnetic and dielectric properties of laminated Ca(Zn1/3Nb2/3)O3-Ni0.8Zn0.2Fe2O4 magneto-dielectric composites. (February 2017) - Lin, Ying; Liu, Xiao; Yang, Haibo; Wang, Fen; Liu, Chun
Graphical abstract: Highlights: Laminated CZN-NZO composites were prepared by solid-state sintering method. The magneto-dielectric property was enhanced by the laminate composite. The permeability of laminated 60%CZN-40%NZO composites is 16.4 at 10 MHz. Abstract: Laminated Ca(Zn1/3 Nb2/3 )O3 (CZN)-Ni0.8 Zn0.2 Fe2 O4 (NZO) composites were prepared by the conventional solid-state sintering method. Compared with the common polycrystalline ceramics, the permeability of the CZN-NZO composites can be much enhanced by the laminated structure. Meanwhile, all the samples show excellent magneto-dielectric properties in a wide frequency range from 10 MHz to 1 GHz. The results indicate that this kind of magneto-dielectric composites can be used in the high frequency communications for the capacitor-inductor integrating devices such as miniaturized antennas, filters and electromagnetic interference suppression devices. The permeabilities of the laminated CZN-NZO composites are well fitted with the Maxwell-Garnett mixing law.